(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study mainly aimed at determining the effect of financial performance on reducing manufacturing costs with its tools (prevention costs, performance costs, defective costs, and quality control costs) in Al-Ahlia Oil Manufacturing Company. The study followed the analytical descriptive approach in its study, and a set of methods including reliance on secondary and primary data through a questionnaire designed and distributed to (62) respondents, from which (57) were retrieved, and (51) questionnaires were valid for analysis, and the research community consisted of a cadre Employees of Al-Ahlia Company for Vegetable Oil Industry in Damascus Governorate at the highest administrative level, then the SPSS program was relied upon as a tool for analyzing the available data. The study reached a number of results, including: The results of the characterization of the statistical statistics for the expressions of the financial performance axis showed that the trend is positive for Al-Ahlia Vegetable Oils Company, and therefore there is a good financial performance for the company under study according to the answers of the sample members. There is a good reduction in manufacturing costs in the company under study according to the answers of the sample members, and there is a significant effect of the financial performance in reducing the manufacturing costs of Al-Ahlia Company for the Vegetable Oil Industry.